The magic of we [videorecording] (Carlsbad, CA : CRM Learning, 2004)
This innovative video program tells the compelling and true story of how management and employees of Snapper Lawn Mowers worked together to create a $65 million company turnaround. Viewers see a team of 25 Snapper employees gather in the main plant on a Saturday morning for a very different kind of meeting. Senior managers, engineers, suppliers, customer service and marketing personnel are assigned one task: Put together 4 lawnmowers from a set of blueprints. It comes down to nuts and bolts - literally! As they work, these diverse teams realize that a universal bolt that was supposed to streamline production is causing more problems than it was supposed to solve. See how they use the 'magic of we' to find the solution. This versatile package contains the Snapper Lawn Mowers story with five different introductions and closings -- each addressing a different topic area: Leadership --- Teamwork --- Problem Solving --- Communication --- Lean Manufacturing. This lets you tailor the training to a variety of audiences or address all of the components together, that led to the success of finding the problem and the solution. Each of the topic areas are revealed within the individual modules. Content : chaptered DVD containing all 5 topic versions of the story. Source : CRM Learning webpage.